How Language and Human Altruism Evolved Hand in Hand — The Backchannel Hypothesis - von Heiseler, Till Nikolaus (Frontiers in Psychology, 2022)
This paper contributes to two debates: the debate about language evolution and the debate about the foundations of human collaboration. While both cooperation and language may give the impression of being adaptations that evolved for the “good of the group”, it is well established that the evolution of complex traits cannot be a direct result of group selection. In this paper I suggest how this tension can be solved: both language and cooperation evolved in a unique two-level evolutionary system which was triggered by a well-documented geological event—the drying out of the climate¬—in East Africa, which subsequently reduced the intermating between groups and thus made it possible that the mechanism that produced differences between groups (including social forms of selection such as female choice) could be the target of natural selection on the group level. If a social form of selection (e.g., sexual selection) produced differences in fitness between groups, the displacement process between groups would indirectly select those forms of social selection that produce groups that would displace all others. The main hypothesis presented in this paper is that, in this situation, a backchannel between the two levels of selection naturally evolves. A backchannel between the two levels would, for example, emerge when sexual selection (or any other form of social selection) was sensitive to the individual’s contribution to the group. Examples of systems utilizing a backchannel are nerve cells being better nourished when used more frequently, enabling them to be conducive to the survival of the whole organism, or a law firm in which all employees get paid to the extent that they contribute to the survival and success of the firm. In both cases, the selection on the higher level informs the selection on the lower level. The aim of the paper is to illuminate these rather opaque claims, to which the reader probably has many objections in this abridged form.